Modern methods of treatment of patients with diabetic foot syndrome - A. V. Pikuza; L. F. Rashitov; M. I. Мitronin; A. A. Akhunzyanov; N. Z. Zaripov; S. G. Gerasimov; A. T. Gabdrakhmanova (Лечащий Врач)
We have analyzed the experience of treatment of 563 patients with diabetic foot syndrome. We have developed an algorithm for the treatment of patients, including modern diagnostic and treatment methods, in particular - endovascular correction of vascular disorders and vacuum aspiration. The use of new technologies in the treatment of patients with diabetic foot syndrome improves their quality of life and social adaptation.